2014
DOI: 10.15453/2168-6408.1111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of International Collaborative Project on Cultural Competence among Occupational Therapy Students

Abstract: Occupational therapy (OT) educators recognize a need to ensure that OT students are culturally competent. The researchers developed the International Collaborative Project on Cultural Competence (ICPCC) to help students understand the impact of cultural context on client care. Entry-level MOT students from a university in the US (N = 18) collaborated with BOT students (N = 4) and advanced MOT students (N = 9) from two universities in India using an online course management system WebCT. The study explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
(13 reference statements)
2
19
0
Order By: Relevance
“…Although student feedback mechanisms did not lend themselves to a specific focus on what students learned about human occupation, they did indicate that experiential learning helped students solidify and apply understandings related to culture. This pilot project affirms recent findings from other universities that local and global experiential learning can increase occupational therapy students' perceived understanding of culture and its impact on occupation and occupational therapy practice 21 . Jeffery argued that "... the educational aspect of [experiential learning] is dependent on the level of processing involved during and after the experience" 10:6 and that a crucial part of experiential education occurs when "... the teacher actively encourages or enables critical reflection on the experience" 10:8 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although student feedback mechanisms did not lend themselves to a specific focus on what students learned about human occupation, they did indicate that experiential learning helped students solidify and apply understandings related to culture. This pilot project affirms recent findings from other universities that local and global experiential learning can increase occupational therapy students' perceived understanding of culture and its impact on occupation and occupational therapy practice 21 . Jeffery argued that "... the educational aspect of [experiential learning] is dependent on the level of processing involved during and after the experience" 10:6 and that a crucial part of experiential education occurs when "... the teacher actively encourages or enables critical reflection on the experience" 10:8 .…”
Section: Discussionsupporting
confidence: 83%
“…The limited occupational therapy scholarship on teaching and learning [15][16][17] offered little guidance for this aspect of the course redesign, but it did suggest that new instructional designs 18 related to online technologies 13,19 and synchronous student collaborations 20 showed promise, especially when coupled with structured reflection 20 . (More recent examples of technology-based international occupational therapy educational collaborations 21 were not published when I undertook the course redesign.) After reviewing existing literature, I worked with a campus instructional designer through the end of 2012 to investigate how the Learning Studio could support international interactions in OCS 372.…”
Section: Redesign #2: Incorporate Global Perspectives Via Synchronousmentioning
confidence: 99%
“…Cultural awareness and competency becomes relevant when utilized to address the needs of culturally diverse client populations (Sood et al, 2014). Research has indicated that occupational therapy practitioners acknowledge the need to understand and develop cultural awareness and competency as a part of education and clinical practice (Cheung et al, 2002;Kale & Hong, 2007;Mu et al, 2010;Munoz, 2007;Murden et al, 2008;Rasmussen et al, 2005;Whiteford & St-Clair, 2002).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
“…The development of cultural competency helps ensure that students and therapists are prepared to recognize a client's personal experience within the cultural context (Sood et al, 2014). Occupational therapists must be aware and sensitive to cultural differences and must be able to consider cultural influences when selecting assessments and occupational interventions to meet the needs of their clients to improve quality of care and avoid any adverse impact (Cheung et al, 2002;Kale & Hong, 2007;Murden et al, 2008;Sood et al, 2014).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
See 1 more Smart Citation